Poly[(N-acryloyl glycine)-co-(acrylamide)]-induced cell growth inhibition in heparanase-driven malignancies - Wasnik K.; Singh G.; Yadav D.D.; Patra S.; Gupta P.S.; Oviya A.; Kumar S.; Pareek D.; Paik P. (My University, 2025)
In the present work, glycine, the monomer N-acryloylglycine (NAG), and polymeric units of poly[(N-acryloylglycine)-co-(acrylamide)] p(NAG-co-Ac) are examined using density functional theory (DFT), and experimental evidence is provided for their use in the therapy of cancer with a poor prognosis. Glycine plays a pivotal role in cell survival, and most anti-cancer agents alter glycine metabolomics and suppress cancer cell proliferation. Herein, we have utilized Frontier Molecular Orbital theory (FMO), and the results revealed that the introduction of acrylamide/divinyl benzene into the glycine-based polymer increased its biological activity by lowering the energy band gap. Heparanase and proteases are important in invasive tumor progression and worsening of prognosis. In this context, we have synthesized co-polymeric p(NAG-co-Ac) and revealed its protease inhibitory activities. It is revealed that the cross-linked homo-polymeric and cross-linked hetero-polymeric tetrameric arrangements inhibit heparanase activity via interacting at heparanase binding domain II (HBDII) with a docking score of ∼−11.08 kcal mol−1 (Ki) and at heparanase binding domain III (HBD III). The bathochromically shifted CD spectrum shows that the hydrogel interacts with heparanase and disturbs the secondary protein structure of the synthesized p(NAG-co-Ac) polymer. It is found that the synthesized p(NAG-co-Ac) hydrogel has anti-proliferative activity, acts as a migratory inhibitor of cancer cells, and favors programmed cell death. Further, the p(NAG-co-Ac) hydrogel exhibited anti-angiogenic behavior. In conclusion, p(NAG-co-Ac), with its anti-angiogenic and anti-tumorigenic capabilities, has a future as a potential anticancer polymer for the treatment of heparanase-driven invasive malignancies without using any additional anticancer drugs, and is promising for cancer treatment. © 2025 The Royal Society of Chemistry.